Relationship of Mother's Knowledge About the Importance of Birth Planning and Complication Prevention Before and After Taking Pregnant Women Classes in Hutaraja Village in 2022 - Yuni Vivi Santri P; Pratiwi Lumbantobing; Susi Amenta Beru Perangin angin (International Archives of Medical Sciences and Public Health, 2022)
The Birth Planning and Complication Prevention Program is a program to increase data coverage and quality of health services for pregnant women and newborns through increasing the active role of families and communities in planning safe deliveries. The class for pregnant women is a study group for pregnant women with a maximum number of 10 participants. This study aims to determine the relationship between maternal knowledge about the importance of delivery planning and prevention of complications before and after attending classes for pregnant women in Hutaraja village in 2022. This research is a quantitative type of research with a cross-sectional approach. The population in this study were all 35 pregnant women, 35 samples with total sampling technique. Data processing used univariate and bivariate analysis using the Chi Square test, the p-value for Knowledge = 0.005. There is a relationship between Mother's Knowledge about the Importance of Delivery Planning and Complication Prevention Before and After Taking Pregnant Women Class. It is hoped that the midwives in Hutaraja Village when Antenatal Care (ANC) explain in detail what is related to the contents of P4K so that pregnant women can know P4K clearly. It is hoped that further research can add to the discourse and literature to conduct further research on the application of pregnant women in the implementation of P4K.